2010
DOI: 10.1038/cmi.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells and their associated cytokines in liver diseases

Abstract: T helper 17 (Th17) cells are a newly identified subset of T helper cells that play important roles in host defense against extracellular bacteria as well as in the pathogenesis of autoimmune disease. The functions of Th17 cells are mediated via the production of several cytokines including interleukin (IL)-17 and IL-22. Recent studies show that the frequency of IL-17+ cells is significantly elevated in a variety of chronic liver diseases including alcoholic liver disease, viral hepatitis and hepatocellular car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 58 publications
5
106
0
Order By: Relevance
“…Otherwise, H. pylori DNA was not detected in the liver of patients with alcoholic cirrhosis and those with autoimmune hepatitis. In agreement with previous studies (Straubinger et al 2003, Algood & Cover 2006, Lafdil et al 2010, we confirmed the strong Th1 proinflammatory response with increased levels of IFN-γ, the Th1 signature cytokine, in these patients. We F: female; M: male; n: number of subjects; SD: standard deviation.…”
Section: Discussionsupporting
confidence: 80%
“…Otherwise, H. pylori DNA was not detected in the liver of patients with alcoholic cirrhosis and those with autoimmune hepatitis. In agreement with previous studies (Straubinger et al 2003, Algood & Cover 2006, Lafdil et al 2010, we confirmed the strong Th1 proinflammatory response with increased levels of IFN-γ, the Th1 signature cytokine, in these patients. We F: female; M: male; n: number of subjects; SD: standard deviation.…”
Section: Discussionsupporting
confidence: 80%
“…IL-17F, originally named for and derived from Th-17-producing T cells, is primarily a proinflammatory cytokine that is involved in innate immunity and autoimmune diseases (reviewed in reference 41). The IL-17 receptor is widely expressed in immune cells, fibroblasts, and epithelial cells, including Huh-7 liver cells (42,43). Our results show that IL-17F induced ISRE-mediated ISG expression, particularly in combination with IFN; these effects required Stat1 signaling and involved endogenous IFN-␤.…”
Section: Discussionmentioning
confidence: 61%
“…IL-17A plays a critical role in neutrophil recruitment, angiogenesis, inflammation, and autoimmune disease that has been previously described extensively (6), including in pulmonary and cardiac fibrosis via IL-17RA and MAPK signaling (8,9). However, very few studies have investigated the role of IL-17A in liver fibrosis (10).…”
mentioning
confidence: 99%